Efektivitas Model Pembelajaran LSQ terhadap Hasil Belajar PKn Peserta Didik Kelas IV SD Negeri 31 Pulau Samatellu Lompo Kab. Pangkep - Rindiani; Usman; M Mirza fatahullah (Primer Edukasi Journal, 2023)
This research aims to describe (1) the implementation of the Learning Start With A Question learning model through the subject of Civics Education in grade IV of State Elementary School 31 Pulau Samatellu Lompo, Pangkep Regency, (2) the learning outcomes of Civics Education for grade IV students of State Elementary School 31 Pulau Samatellu Lompo, Pangkep Regency before and after the implementation of the Learning Start With A Question model, and (3) to analyze the effectiveness of the Learning Start With A Question model in teaching Civics Education towards the learning outcomes of grade IV students of State Elementary School 31 Pulau Samatellu, Pangkep Regency.The research design used in this study was a pre-experimental design with a "One Group pretest-Posttest" design. The implementation of learning activities using the Learning Start With A Question learning model in the first meeting was categorized as good with a percentage of 66%, while in the second meeting it was categorized as very good with a percentage of 88%, and in the third meeting it was categorized as excellent with a percentage of 100%. The assessment of learning outcomes showed that the average score before the implementation of the Learning Start With A Question learning model was 42, while the average score after the implementation of the Learning Start With A Question model was 85. Therefore, the implementation of the Learning Start With A Question model is effective in improving the Civics Education learning outcomes of grade IV students of State Elementary School 31 Pulau Samatellu Lompo, Liukang Tupabbiring Utara District, Pangkep Regency.